Ambiguity, bureaucracy and certainty: The ABCs of enabling water self-sufficiency. Issue 2 (1st January 2016) - Leong, Ching; Qian, Neng
Abstract: Ambiguity has often been taken as the bete noir of policy implementation, with policy intent stymied by unclear goals and lack of clarity about processes. This paper argues that, given sufficient apparent certainty about strategic intents, ambiguity can actually be an enabling factor that allows for quick adaptations. It goes do in three ways – first, ambiguity allows the creation of faint paths that are overwritten in the light of new decisions; second and relatedly, this enables the bureaucracy to take more risks, in light of the relatively low sunk costs; third, ambiguity allows for experiments with fuzzy parameters of success, which contributes to innovation. In all three, the role of learning is crucial. This thesis of ambiguity as enabler of learning by bureaucrats is tested in the case of water security in Singapore, which faced economic, technology and security ambiguities. There is a bureaucratic tendency to react to ambiguity with a search for more information and clarity. However because of the ambiguity-enabled learning, Singapore through a very roundabout and messy implementation process, was able to overcome a key strategic vulnerability.